Profit Taxation and Capital Accumulation in Dynamic Oligopoly Models - Luca Lambertini; Massimo Baldini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
We illustrate two differential oligopoly games using, respectively, the capital accumulation dynamics `a la Solow-Nerlove-Arrow, and the capital accumulation dynamics `a la Ramsey. In both settings, we evaluate the effects of (gross) profit taxation, proving that there exist tax rates yielding the same steady state social welfare as under social planning. Contrary to the static approach, our dynamic analysis shows that, in general, profit taxation affects firms' decisions concerning capital accumulation and sales. In particular, it has pro-competitive effects provided that the extent of delegation is large enough.
Keywords: 330